ETHNOBOTANY OF MEDICAL PLANTS IN THE COMMUNITIES AROUND THE GUNUNG LEUSER NATIONAL PARK RESORT CINTA RAJA, SUMATERA UTARA PROVINCE - Amrul, Hanifah Mutia Z.N.; Huda, Muhammad Komarul; Hutasoit, Lembang Ferdinand; Basuki, Rangga Bayu (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The ethnobotany research on medicinal plants around Gunung Leuser National Park aims to determine the types of medicinal plants commonly used by the community around the TNGL area of the Cinta Raja resort and to determine the types of medicinal plants originating from the GLNP area. This study used a survey method by choosing one key person. The method used to collect plant species in Kawan TNGL is the cruising method and determining the location of the meeting point of medicinal plants. Data analysis using descriptive method. The study found 54 types of plants used as traditional medicine by the community around the TNGL Resort Cinta Raja area. The most widely used medicinal plant species were from the Zingiberaceae group, with as many as 10 species. The most common types of medicinal plants taken from forest areas are yellow roots.